Mini Review: The Efficiency of Sugar Mills in East Java Province - Rachmadhan, Aditya Arief; Wijayati, Prasmita Dian; Hariputra, Akbar; Qalsum, Ummy; Manihuruk, Ekamonika; Asri, Dian; Lainatussifa (UPN Veteran Jatim, 2025)
East Java Province is recognized as one of Indonesia’s main producers of the white sugar (plantation white sugar/gula kristal putih). However, The closure of these sugar mills raises an important question about the mills efficiency. The urgency of this study lies in the need to develop a comprehensive literature review that synthesizes existing findings on the production efficiency of East Java's sugar mills. The research was conducted in April 2025, using the literature review method. The results shows that the efficiency of sugar mills in East Java Province remains below the optimal threshold, both technically and economically. This inefficiency is caused by several factors, including inconsistent sugarcane supply, outdated factory machinery, and socio-economic challenges such as price policy and the low welfare of farmers. Inefficiency has become one of the key reasons behind the closure of several sugar mills in East Java, particularly those owned by PTPN X and PTPN XI.